Gender-Based Violence as a Public Health Crisis: Consequences for Nigerian Women and Society - Ojemeiri Karl Airaoje; Chinelo Ebele Uchendu; Omolara Oluwabusayo Akin-Odukoya; Eric Msughter Aondover; Aruaye Afeye Obada (Britain International for Academic Research (BIAR) Publisher, 2025)
Gender-based violence (GBV) has emerged as a critical public health crisis worldwide, particularly in developing nation like Nigeria. The pervasive nature of GBV poses significant challenges to public health, human rights, and socio-economic development. Therefore, Gender-Based Violence (GBV) in Nigeria remains a pervasive issue with far-reaching physical, mental, societal, and economic consequences. This study investigates the primary forms and prevalence rates of GBV, its physical and mental health impacts, societal and economic consequences, and mitigation strategies. Findings reveal that physical violence, sexual violence, emotional abuse, and harmful traditional practices are the most prevalent forms of GBV, with significant prevalence rates among women aged 15–49. The study revealed that these acts of violence result in severe physical injuries, reproductive health complications, and chronic illnesses, alongside profound psychological impacts such as PTSD, depression, anxiety, and suicidal tendencies. The findings revealed that societal consequences of GBV include disrupted family structures, educational disparities, and social instability, while the economic implications range from reduced productivity and increased healthcare costs to the perpetuation of poverty. Also, cultural norms, patriarchy, stigma, and limited access to healthcare exacerbate the effects of GBV, creating barriers for survivors seeking justice and support. The study recommends the launching of nationwide awareness campaigns to challenge cultural norms that perpetuate GBV through the involvement of traditional and religious leaders, educators, and influencers to foster community-wide behavioral change and increase awareness about the rights of women and the consequences of GBV.